Manajemen Kasus Pemenuhan Kebutuhan Oksigenasi pada Pasien Tuberkulosis Paru - Muhaimin Saranani; Dian Yuniar Syanti Rahayu; Ketrin Ketrin (Poltekkes Kemenkes Kendari, 2019)
Pulmonary tuberculosis is an infectious disease that attacks the lung parenchyma, caused by Mycobacterium tuberculosis (Somantri, 2009). In 2017 in Southeast Sulawesi, 2,587 new cases of BTA (+) were found. In 2016 in Kendari City Hospital, 229 cases of pulmonary tuberculosis were obtained, while in 2017 there were 286 cases (Medical Records and SIRS of Kendari City). Objective: Carry out nursing care for pulmonary tuberculosis patients in fulfilling oxygenation needs in the Lavender Room at the Kendari City Hospital. Methods: In this study, researchers used a descriptive study, namely a case study. Result: Nursing diagnosis, namely ineffective airway clearance associated with excessive mucus. After 3x24 hours of action, the results showed: the patient did not experience shortness of breath, breathing 20 times / minute, no additional breath sounds and the patient was able to cough effectively without the help of the nurse's instructions. Bottom Line: An effective cough action can help drain secretions and reduce chest pain.